Implementation of Philsin College Foundation, Inc. Integrated Library System - Cao, Danilyn B. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
New generation of librarians are striving hard to transmogrify traditional set-up of libraries by venturing to available free integrated library systems. The main objective of this project is to automate the current manual system of Philsin College Foundation, Inc. Library by implementing the Infolib integrated library system. The main instrument that was used in this project is a survey through use of questionnaires. This method helped the researcher to gather and determine satisfaction of the PCFI community regarding the services being provided by the library.